A mineralogical characterization of biogenic calcium carbonates precipitated by heterotrophic bacteria isolated from cryophilic polar regions. Issue 6 (24th September 2014) - Ronholm, J.; Schumann, D.; Sapers, H. M.; Izawa, M.; Applin, D.; Berg, B.; Mann, P.; Vali, H.; Flemming, R. L.; Cloutis, E. A.; Whyte, L. G.
Abstract: Precipitation of calcium carbonate (CaCO3(s) ) can be driven by microbial activity. Here, a systematic approach is used to identify the morphological and mineralogical characteristics of CaCO3(s) precipitated during the heterotrophic growth of micro‐organisms isolated from polar environments. Focus was placed on establishing mineralogical features that are common in bioliths formed during heterotrophic activity, while in parallel identifying features that are specific to bioliths precipitated by certain microbial phylotypes. Twenty microbial isolates that precipitated macroscopic CaCO3(s) when grown on B4 media supplemented with calcium acetate or calcium citrate were identified. A multimethod approach, including scanning electron microscopy, high‐resolution transmission electron microscopy, and micro‐X‐ray diffraction (μ‐XRD), was used to characterize CaCO3(s) precipitates. Scanning and transmission electron microscopy showed that complete CaCO3(s) crystal encrustation of Arthrobacter sp. cells was common, while encrustation of Rhodococcus sp. cells did not occur. Several euhedral and anhedral mineral formations including disphenoid‐like epitaxial plates, rhomboid‐like aggregates with epitaxial rhombs, and spherulite aggregates were observed. While phylotype could not be linked to specific mineral formations, isolates tended to precipitate either euhedral or anhedral minerals, but not both. Three anhydrous CaCO3(s) polymorphs (calcite, aragonite, and vaterite) were identified by μ‐XRD, and calcite and aragonite were also identified based on TEM lattice‐fringe d value measurements. The presence of certain polymorphs was not indicative of biogenic origin, although several mineralogical features such as crystal‐encrusted bacterial cells, or casts of bacterial cells embedded in mesocrystals are an indication of biogenic origin. In addition, some features such as the formation of vaterite and bacterial entombment appear to be linked to certain phylotypes. Identifying phylotypes consistent with certain mineralogical features is the first step toward discovering a link between these crystal features and the precise underlying molecular biology of the organism precipitating them.